The integrin-linked kinase-PINCH-parvin complex supports integrin αIIbβ3 activation. - Shigenori Honda; Hiroko Shirotani-Ikejima; Seiji Tadokoro; Yoshiaki Tomiyama; Toshiyuki Miyata (PLoS ONE, 2013)
Integrin-linked kinase (ILK) is an important signaling regulator that assembles into the heteroternary complex with adaptor proteins PINCH and parvin (termed the IPP complex). We recently reported that ILK is important for integrin activation in a Chinese hamster ovary (CHO) cell system. We previously established parental CHO cells expressing a constitutively active chimeric integrin (αIIbα6Bβ3) and mutant CHO cells expressing inactive αIIbα6Bβ3 due to ILK deficiency. In this study, we further investigated the underlying mechanisms for ILK-dependent integrin activation. ILK-deficient mutant cells had trace levels of PINCH and α-parvin, and transfection of ILK cDNA into the mutant cells increased not only ILK but also PINCH and α-parvin, resulting in the restoration of αIIbα6Bβ3 activation. In the parental cells expressing active αIIbα6Bβ3, ILK, PINCH, and α-parvin were co-immunoprecipitated, indicating the formation of the IPP complex. Moreover, short interfering RNA (siRNA) experiments targeting PINCH-1 or both α- and β-parvin mRNA in the parent cells impaired the αIIbα6Bβ3 activation as well as the expression of the other components of the IPP complex. In addition, ILK mutants possessing defects in either PINCH or parvin binding failed to restore αIIbα6Bβ3 activation in the mutant cells. Kindlin-2 siRNA in the parental cells impaired αIIbα6Bβ3 activation without disturbing the expression of ILK. For CHO cells stably expressing wild-type αIIbβ3 that is an inactive form, overexpression of a talin head domain (THD) induced αIIbβ3 activation and the THD-induced αIIbβ3 activation was impaired by ILK siRNA through a significant reduction in the expression of the IPP complex. In contrast, overexpression of all IPP components in the αIIbβ3-expressing CHO cells further augmented THD-induced αIIbβ3 activation, whereas they did not induce αIIbβ3 activation without THD. These data suggest that the IPP complex rather than ILK plays an important role and supports integrin activation probably through stabilization of the active conformation.